Citizen politics : public opinion and political parties in advanced industrial democracies - Dalton, Russell J. (CQ Press, 2008)
Now, more than ever, people drive the democratic process. What people think of their government and its leaders, how (or whether) they vote, and what they do or say about a host of political issues greatly affect the further strengthening or erosion of democracy and democratic ideals. With helpful restructuring, the new fifth edition of Citizen Politics is even more student-friendly while continuing to offer the only truly comparative study of political attitudes and behavior in the United States, Great Britain, France, and Germany.\In addition to its comprehensive, thematic examination of political values, political activity, voting, and public images of government within a cross-national context, Citizen Politics now explores new forms of political activity, such as Internet-based activism, and new forms of political consumerism. All of the chapters have been updated with the latest research and empirical evidence, including new data from the Comparative Study of Electoral Systems project, the World Values Survey, the International Social Survey Program, and the British and German national election studies. Further, Dalton devotes more attention to current academic debates over the decline of participation, the erosion of political support, and the implications for democracy.